Effectiveness of aromatic plant species for repelling and preventing oviposition of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). (31st October 2017) - Wagan, T. A.; He, Y. P.; Long, M.; Chakira, H.; Zhao, J.; Hua, H. X.
Abstract: This study assesses the effectiveness of essential oils for repelling whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), and deterring oviposition. We evaluated essential oils from four plants: Curcuma longa (Zingiberaceae), Litsea cubeba (Lauraceae), Piper nigrum (Piperaceae) and Zanthoxylum bungeanum (Rutaceae), under laboratory and glasshouse conditions. In the laboratory, ethanol‐extracted essential oils were applied uniformly on both sides of a tomato leaf in the treatment groups, and the same volume of liquid but without essential oil was used for the control. Results showed that essential oils from L. cubeba, P. nigrum, C. longa and Z. bungeanum provided some repellency of whiteflies and reduced oviposition. Oils from L. cubeba repelled adult females (69.14% and 62.49% repellency at 24 and 48 hr, respectively), and oils from C. longa deterred oviposition (68.46% and 65.94% at 24 and 48 hr exposures, respectively). In the glasshouse, potted tomato plants with eight leaves were sprayed with treatments and control material. Five‐day‐old adult female whiteflies were released in a cage between both pots. Essential oils from L. cubeba repelled females 54.77 at 24 hr and P. nigrum 44.37% at 48 hr whereas oils from P. nigrum reduced oviposition by 43.35 at 24 hr and Z. bungeanum 21.08% at 48 hr, under glasshouse conditions. Essential oils show potential to be used to reduce feeding and oviposition, and thus being important components of integrated pest management programs. However, future research is needed to investigate individual compounds of these oils against whitefly, and to enhance their effectiveness.